Effect of seat positions on discomfort, muscle activation, pressure distribution and pedal force during cycling. (April 2016) - Verma, Rachita; Hansen, Ernst A.; de Zee, Mark; Madeleine, Pascal
Abstract: The aim of this study was to measure and analyse discomfort and biomechanics of cycling, i.e., muscle activation, centre of pressure of seat pressure profiles and pedal forces as a function of seat position. Twenty-one recreationally active individuals cycled for 10 min at 100 W on an ergometer cycle using five different seat positions. The neutral position was considered as basic seat position and was compared with upward, downward, forward and backward seat positions. The initial bout was repeated at the end of the recording session. Discomfort increased for upward and backward condition compared with neutral ( P  < 0.05). Normalized surface electromyography from gastrocnemius decreased in the downward and forward position but increased in the upward and backward position. The minimum force became less negative for forward position compared with neutral seat position ( P  < 0.05). The degree of variability of centre of pressure increased in the upward and backward position and the entropy of the centre of pressure of sitting posture for backward position decreased compared with neutral seat position ( P  < 0.05). The present study revealed that consecutive changes of seat position over time lead to increase in discomfort as well as alterations of the biomechanics of cycling.